The Dreams of a Bear: Animal Traditions in the Old Norse-Icelandic Context - Ramos, Eduardo, 1990- (2014)
Medieval Icelandic literature is rich with animal references. We often read of characters appearing in dreams as animals, taking the shape of animals, or even simply fighting like ferocious beasts. Particularly prominent are the traditions of animal warriors, such as berserkir, and animal doubles embodied by fylgjur and those who are said to be hamrammr. Traces of these animal traditions can be found across the Old Norse sphere, but they are most persistent in the literature of Iceland. Despite the changes in perspective to pre-Christian material that took place over the centuries, the versatility of these animal traditions allowed them to remain current and relevant in Iceland. By conducting a study of the character Bǫðvarr bjarki, with particular focus on his shape changing episode in Hrólfs saga kraka, this thesis demonstrates the resilience and versatility that allowed these rich animal traditions to endure for centuries within the Old Norse-Icelandic context. Gjarnan er vísað til dýra í íslenskum miðaldabókmenntum. Oft koma sögupersónur fram í draumum sem dýr, taka á sig ásýnd dýra eða einfaldlega berjast eins og þau væru dýr. Einkar eftirtektarverðar eru frásagnir af hermönnum sem hafa dýrsleg einkenni, t.d. berserkir, en einnig fylgjur í gervi dýra auk þeirra persóna sem sagðar eru hamrammar. Menjar um þessa sagnahefð má finna víða í fornnorrænni menningu en eru mest áberandi í bókmenntum Íslands. Þó að afstaðan til hins forkristna efnis hafi breyst í gegnum tíðina, gerði sveigjanleiki sagnaminna um hamskipti af þessu tagi þeim kleift að halda gildi sínu í íslenskum bókmenntum eftir því sem sögu þeirra vatt fram. Með því að rannsaka sérstaklega sögupersónuna Bǫðvar bjarka og hamskiptum hennar í Hrólfs sögu kraka, er reynt í ritgerðinni að sýna fram á sveigjanleika en einnig varðveislu þessarar hefðar um aldaraðir í samhengi norrænna og íslenskra miðaldabókmennta.